[Math] Simplify Boolean Expression Given Truth Table

boolean-algebra

Truth Table

I have the truth table above which gives the minterm expression

$$F = (\neg a \land \neg b \land c) \lor (\neg a \land b \land \neg c) \lor (a \land \neg b \land \neg c) \lor (a \land b \land c)$$

but I'm unsure how to simplify it using boolean algebra to prove it is the XOR of a, b, and c.

Best Answer

We know that $x \veebar y = (\neg x \land y) \lor (x \land \neg y)$.

Note that, by combining terms with $a$ and combining terms with $\neg a$:

$$\begin{align*} F &= (\neg a \land \neg b \land c) \lor (\neg a \land b \land \neg c) \lor (a \land \neg b \land \neg c) \lor (a \land b \land c) \\ &= (\neg a \land (\neg b \land c)) \lor (\neg a \land (b \land \neg c)) \lor (a \land (\neg b \land \neg c)) \lor (a \land (b \land c)) \\ &= (\neg a \land ((\neg b \land c) \lor (b \land \neg c))) \lor (a \land ((\neg b \land \neg c) \lor (b \land c))) \\ &= (\neg a \land (b\veebar c)) \lor (a \land \neg((\neg b \land c) \lor (b \land \neg c))) \\ &= (\neg a \land (b\veebar c)) \lor (a \land \neg(b\veebar c)) \\ &= a \veebar (b \veebar c) = a \veebar b \veebar c \end{align*}$$

Related Question